Menthacarin, a proprietary combination of peppermint and caraway oil, alters cultured human fecal microbiota composition, resulting in increased SCFA production - Lehner, Martin D.; Ulsemer, Philippe; Christochowitz, Sandra (Frontiers in Pharmacology, 2025)
BackgroundDisruptions in the gut microbiota metabolism may contribute to the pathophysiology of gut–brain interaction disorders, and correction of intestinal dysbiosis is considered a promising therapeutic approach. Menthacarin, a proprietary fixed combination of Mentha x piperita L. and Carum carvi L. essential oils, is used clinically for the treatment of functional dyspepsia and irritable bowel syndrome. Rodent model data indicate that treatment effects of Menthacarin on visceral hypersensitivity could be mediated via the normalization of gut dysbiosis. However, the impact of Menthacarin on human bacterial gut microbiota has not yet been studied.AimThe aim of the present study was to assess whether Menthacarin affects the composition and metabolic activity of human fecal microbiota.MethodsFecal slurry samples from 10 healthy volunteers were cultivated for 36 h under anoxic conditions with and without Menthacarin. Relative bacterial abundance at the phylum and genus levels was evaluated using 16S rRNA metagenomic analysis. Short-chain fatty acids (SCFAs) in the supernatants were measured using the LC-MS technology.ResultsMenthacarin induced robust changes in microbial composition at both the phylum and genus levels among the 10 donor microbiomes. The relative abundance of Firmicutes (+13.6 ± 8.6%) and Actinobacteria (+54.9 ± 47.6%) significantly increased, whereas that of Bacteroidetes (−27.7% ± 21.9%) and Proteobacteria (−25.7% ± 12.3%) significantly decreased in the presence of Menthacarin. At the genus level, the most notable changes were significant increases in Bifidobacterium (+105.1 ± 78.4%) and several SCFA-producing genera accompanied by a significant decrease in genera containing members involved in pro-inflammatory processes. In addition, Menthacarin significantly increased the levels of several SCFAs, namely, propionate, butyrate, isobutyrate, valerate, and isovalerate.ConclusionMenthacarin alters the microbiota composition and enhances SCFA production in human microbiota samples under in vitro conditions. These effects may contribute to the clinical benefits observed with Menthacarin treatment.